Ana González Neira, Prensa del exilio republicano 1936-1977. Andavira Editora, Santiago de Compostela, 2010; 251 pp. - Valender, James (Nueva Revista de Filología Hispánica (NRFH), 2012)
Se reseña el libro: Prensa del exilio republicano 1936-1977.